Traffic Patterns and Emergency Medical Services Prenotification Transport Estimates in Trauma Activations [Letter] - Luthfiyah S; Triwiyanto T; Ismath M (Open Access Emergency Medicine)
Sari Luthfiyah,1 Triwiyanto Triwiyanto,2 Mohammed Ismath3 1Department of Nursing, Poltekkes Kemenkes Surabaya, Surabaya, Indonesia; 2Department of Electromedical Technology, Poltekkes Kemenkes Surabaya, Surabaya, Indonesia; 3Inamdar Multi-Specialty Hospital, Pune, Maharashtra, IndiaCorrespondence: Sari Luthfiyah, Email sarilut@poltekkesdepkes-sby.ac.id